Agricultural productivity growth in Vietnam in reform and post-reform period - Linh Hoang Vu; Le Quy Dinh Nguyen (Cogent Economics & Finance, 2021)
This paper applies the Malmquist productivity index method to measure total factor productivity (TFP) growth in Vietnamese agriculture using panel data from 60 provinces in Vietnam during 1985-2000 when Vietnam implemented widespread de-collectivization, trade liberalization, and reformed her agriculture sector. This study indicates that most of the early growth in Vietnamese agriculture during the first reform period 1985-1990 was due to TFP growth in response to incentive reforms. During the second reform period 1990-1995, the growth rate of TFP fell, and Vietnam's agricultural growth was mainly caused by drastic investment in capital. In the post-reform period (1995-2000), TFP growth increased again, though still much lower than 1985-1990. Overall, the TFP growth rate in the whole period is estimated at 1.96 percent, contributing to 38% of Vietnam's agricultural growth.
Keywords: O13; Q10; R30; 330; agriculture; bootstrap; DEA; efficiency; Malmquist; productivity; Vietnam